Phosphorylated 3-Heteroarylcoumarins and their use in fluorescence microscopy and nanoscopy - Nizamov, Shamil; Hell, Stefan (Chemistry - a European journal, 2012)
Photostable and bright fluorescent dyes with large Stokes shifts are widely used as markers in far-field optical microscopy, but the variety of useful dyes is limited. The present study introduces new 3-heteroaryl coumarins decorated with a primary phosphate group (OP(O)(OH)2) attached to C-4 in 2,2,4-trimethyl-1,2-dihydroquinoline fragment fused with the coumarin fluorophore. The general synthetic route is based on the Suzuki reaction of 3-bromocoumarines with hetarylboronic acids followed by oxidation of the methyl group at the CC bond with SeO2 (to an aldehyde), reduction with NaBH4 (to an alcohol), and conversion into a primary phosphate. The 4 position in the coumarin system may be unsubstituted or bear a methyl group. Phosphorylated coumarins were found to have high fluorescence quantum yields in the free state and after conjugation with proteins (in aqueous buffers). In super-resolution light microscopy with stimulated emission depletion (STED), the new coumarin dyes provide an optical resolution of 40-60 nm with a low background signal. Due to their large Stokes shifts and high photostability, phosphorylated coumarins enable to combine multilabel imaging (using one detector and several excitation sources) with diffraction unlimited optical resolution.
Gesehen am 31.10.2018